THE ROLE OF APIP IN SUPPORTING EFFECTIVE SDGS IMPLEMENTATION AT THE LOCAL GOVERNMENT LEVEL - Prasetyo, Agus; Suryani, Pesi; Gaol, Lasando Lumban (Jurnal Aplikasi Akuntansi, 2026)
This study examines the influence of the Government Internal Supervisory Apparatus (APIP) on the effectiveness of Sustainable Development Goals (SDGs) implementation in the Samarinda City Government. Using a quantitative descriptive–analytical method, data were collected from 54 respondents, comprising APIP personnel and SDGs program managers, through a Likert-scale questionnaire, complemented by secondary data on audit frequency, recommendations, follow-up rates, and budget realization. Regression results indicate that APIP’s role has a significant positive effect on the effectiveness of SDGs implementation (β = 0.57, p = 0.010), although the model’s explanatory power is modest (R² = 0.121). Triangulation confirms that stronger audit intensity and follow-up correlate with higher SDGs performance. Theoretically, this study extends the literature on public sector auditing by contextualizing APIP’s contribution to sustainable governance, positioning it as both a compliance enforcer and a driver of policy accountability. Practically, the results underscore the need to strengthen APIP’s institutional capacity through auditor competence development, the integration of SDG indicators into audit planning, and the implementation of digital monitoring systems. These findings provide a foundation for further studies using multi-variable or mixed-method approaches to capture broader institutional dynamics in achieving SDGs at the local government level.